STUDENTS’ PERCEPTION ON BLENDED LEARNING IN ENGLISH CLASS AT POST COVID CONDITION - aryawira Pratama (ENGLISH, 2023)
This research aims to explore the perception of English students at an Islamic University in Jambi regarding the use of Blended Learning in the post-Covid condition. Blended Learning, which combines traditional face-to-face instruction with online learning, has been shown in previous research to have a significant impact on learning, particularly during the Covid-19 pandemic. To assess the participants' perception of Blended Learning, a survey method was employed, utilizing a questionnaire as a tool to gather data. The questionnaire focused on three dimensions: Blended Learning benefits, Blended Learning challenges, and the assessment of course quality based on Blended Learning. The findings of this research indicate that the participants provided an average assessment of the benefits associated with Blended Learning, a high assessment of the challenges faced when implementing this approach, and an average assessment of the course quality based on Blended Learning. These results shed light on the English students' perceptions of Blended Learning in the context of post-Covid education.